2020
DOI: 10.1177/2399808320949885
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between spatial morphology characteristics and scenic beauty preference of landscape open space unit by using point cloud data

Abstract: To explore the relationship between the objective morphological features and subjective scenic beauty preference of landscape open space units, this study improves the research method for morphology quantification, scenic beauty preference survey and relationship analysis. Fourteen morphology factors representing the features of boundary, domain and enclosure are quantified based on the point cloud data of 35 open space units. Scenic beauty evaluation is conducted online with dynamic panoramic photos. Principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Recently, quantitative research surfaced which added further support for three of the tendencies found by the present article. Tall buildings and skylines can be statistically traced back to oppressive sensations for the viewer (Asgarzadeh et al, 2012) and smaller scenic beauty (Wang et al, 2021). Those authors also found that higher proportions of vegetation and the presence of trees mitigate the aforementioned negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, quantitative research surfaced which added further support for three of the tendencies found by the present article. Tall buildings and skylines can be statistically traced back to oppressive sensations for the viewer (Asgarzadeh et al, 2012) and smaller scenic beauty (Wang et al, 2021). Those authors also found that higher proportions of vegetation and the presence of trees mitigate the aforementioned negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Of the quantitative studies, only Calafiore (2020) and Li et al (2021) used field data to obtain a pleasantness indicator, respectively, a beauty index and a street quality index. Quantitative work exists on the impact of isolated geometric elements on pleasantness (Asgarzadeh et al, 2012; D’Acci, 2014; Lee, 2021; Wang et al, 2021), but none of these works have evaluated the combined landscape at the neighborhood scale. Thus, the literature on quantitative evaluation of layout pleasantness is very much in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the spatial 3D model obtained by oblique photography is exported in the format of point cloud. The point cloud data can be classified, edited, segmented, and extracted, which provides the possibility for the extraction of structural elements (Urech et al, 2020; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They offer means to create and maintain realistic digital city models. Light Detection and Ranging (LiDAR) or photogrammetry offers point clouds with reliable spatial information for a wide range of built environment applications already (Sepasgozar et al, 2016;Wang et al, 2020a;Wang et al, 2021b;Xu et al, 2021c). Supported by advanced technology, now it is possible to reconstruct 3D realistic tree models from point clouds (Barton et al, 2020;Boufidou et al, 2011;Eusuf et al, 2020;Homainejad et al, 2022;Wang et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%